Athar al-Ta’līm al-Iktisyā fi Tarkīb al-Jumal al-΄iḍāfiyyah wa Na‘tiyyah fī al-Insyā’ al-Ḥurr (Dirāsah Tajrībiyyah bi Ma‘had Jemalā ‘Amal) - T Iskandar (DAYAH: Journal of Islamic Education, 2018)
΄Iḍafiah and Na’tiyah specifically Nahwu are crucial elements in arabic learning that has to be learned by students before they produce the perfect Insyᾱ’ al-Ḥurr. The students of Jeumala Amal not only found difficulties in learning ΄Iḍafiah and Na’tiyah but got bored as well. Thus, students had a very low ability. It was caused by the disagreement between method used by teacher and students' condition. Based on these problems, Discovery Method was selected by researcher in order to increase students' ability in ΄Iḍafiah and Na’tiyah. The purposes of this research are To identify students' response toward Discovery Method in learning, and to find out students' ability to produce Insyᾱ’ al-Ḥurr with the right ΄Iḍafiah and Na’tiyah arrangement. Quantitative supported by qualitative approach along with experimental method was used by researcher. Purposive sampling was used to find the fifth graders of 5 IPA1 that was consisted of 34 students. The result is that the use of Discovery Method in learning ΄Iḍafiah and Na’tiyah was effective and it gave a good impact on students of Jeumala Amal College, which the result from the T-hitung related calculation is greater than T-tabel result, that is 2,83>1,99.